Reduced Cancer Incidence in Huntington's Disease: Analysis in the Registry Study - Mcnulty, Paul; Pilcher, Richard; Ramesh, Raviram; Necuiniate, Renata; Hughes, Alis; Winkler, Jürgen; Farewell, Daniel; Holmans, Peter; Jones, Lesley (Journal of Huntington's Disease, 2018)
Background: People with Huntington's disease (HD) have been observed to have lower rates of cancers. Objective: To investigate the relationship between age of onset of HD, CAG repeat length, and cancer diagnosis. Methods: Data were obtained from the European Huntington's disease network REGISTRY study for 6540 subjects. Population cancer incidence was ascertained from the GLOBOCAN database to obtain standardised incidence ratios of cancers in the REGISTRY subjects. Results: 173/6528 HD REGISTRY subjects had had a cancer diagnosis. The age-standardised incidence rate of all cancers in the REGISTRY HD population was 0.26 (CI 0.22-0.30). Individual cancers showed a lower age-standardised incidence rate compared with the control population with prostate and colorectal cancers showing the lowest rates. There was no effect of CAG length on the likelihood of cancer, but a cancer diagnosis within the last year was associated with a greatly increased rate of HD onset (Hazard Ratio 18.94, p < 0.001). Conclusions: Cancer is less common than expected in the HD population, confirming previous reports. However, this does not appear to be related to CAG length in HTT. A recent diagnosis of cancer increases the risk of HD onset at any age, likely due to increased investigation following a cancer diagnosis.
CRIS-Team Scopus Importer:2021-07-19
Keywords: cancer; Huntington's disease; neurodegeneration; trinucleotide repeat